Response to COVID-19: Minimizing Risks, Addressing Challenges and Maintaining Operations in a Complex Academic Radiology Department. Issue 4 (July 2020) - Pedrosa, Ivan; Browning, Travis; Kwon, Jeannie K.; Morriss, Michael; Matsler, Lacy; Pinho, Marco C.; Lamus, Daniel; Pillai, Anil; Karow, Sweta Patel; Garinn, Jon; Brewington, Cecelia; Zeikus, Eric; et al.
Abstract : Abstract: The coronavirus disease 2019 (COVID-19) pandemic has necessitated rapid response plans to minimize risks of infection in the workforce while ensuring maintenance of essential functions of radiology departments. Plan adoption is, however, challenged by the need to coordinate with institutional efforts, a rapidly expanding number of patients, and the diversity of clinical and administrative functions in the department. Here, we describe the implementation of a response plan in an academic radiology department, challenges encountered, and tactics used to address these challenges.